ANALISA TENTANG LEGALITAS PERSIDANGAN PEMBUKTIAN MENURUT PASAL 25 PERMA NOMOR 1 TAHUN 2019 TENTANG ADMINISTRASI PERKARA DAN PERSIDANGAN DI PENGADILAN SECARA ELEKTRONIK - Mutiara Seroja; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The world has entered the Era of the Industrial Revolution, wherecomputerization and digitalization processes have occurred and have affectedalmost all aspects of human life, including the legal system. This causes courtinstitutions to rely on technology to support the continuity of legal services tojustice seekers. This online trial applies to both criminal and civil cases. For civiltrials, use a special application called E-Court or E-Litigation.The type of research used by researchers is normative legal research orwhat is known as "legal research". Normative law research uses normative casestudies in the form of legal behavior products, for example studying laws. Thisstudy examines the main issues in accordance with the scope and identification ofproblems through a statutory approach (statute approach). The data collectiontechnique used in normative legal research is the library research method, namelyusing the library as a means of collecting data, by studying books as referencematerials related to the problems to be studied.The conclusions that can be obtained from the research results are First,the arrangements for electronic evidentiary trials have been regulated in SupremeCourt Regulation Number 1 of 2019 concerning Case Administration and Trialsin Electronic Courts. As for other regulations, namely Law Number 11 of 2008 inconjunction with Law Number 19 of 2016 concerning Information and ElectronicTransactions (ITE) related to the recognition of electronic documents which areequivalent to documents made on paper still have the power of proof of electronicdocuments in case practice Civil law is equated with the strength of writtenevidence (letters). Second, written evidence contained in electronic evidence trialswhen referring to article 1888 of the Civil Code can still be equated with thestrength of written evidence (letters) as long as the copies and quotations are inaccordance with the originals which can always be ordered to be shown.Electronic devices and/or electronic documents are considered valid as long asthe information contained therein can be accessed, displayed, guaranteed forintegrity, and can be accounted for so that it can explain a situation.Keywords: Trial, Evidence, Electronics